2012
DOI: 10.3103/s1063457612050085
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanostructuration on compressibility of cubic BN

Abstract: ra ak ke ev vy yc ch h, , P P. . M Mu un ns sc ch h (Paris, France)

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It has also been demonstrated that the density and me-chanical properties of BN can be tuned by constructing a mixture of its cubic and hexagonal phases. 7 There have been extensive theoretical and experimental studies on the structure 8,9 , stability [10][11][12] , EOS [13][14][15][16][17][18] , melting and phase diagram [19][20][21][22] , and mechanical [23][24][25] , optical 26,27 , thermodynamic 14,25,28,29 , and transport 30,31 properties of BN and its polymorphs. The phase transformation of rhombohedral BN (r-BN) was found to be dependent on the pressure transmitting medium 12 , and the transition of h-BN into a wurtzite phase (w-BN) under plastic shear may be dramatically different from that under hydrostatic pressures 32,33 .…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that the density and me-chanical properties of BN can be tuned by constructing a mixture of its cubic and hexagonal phases. 7 There have been extensive theoretical and experimental studies on the structure 8,9 , stability [10][11][12] , EOS [13][14][15][16][17][18] , melting and phase diagram [19][20][21][22] , and mechanical [23][24][25] , optical 26,27 , thermodynamic 14,25,28,29 , and transport 30,31 properties of BN and its polymorphs. The phase transformation of rhombohedral BN (r-BN) was found to be dependent on the pressure transmitting medium 12 , and the transition of h-BN into a wurtzite phase (w-BN) under plastic shear may be dramatically different from that under hydrostatic pressures 32,33 .…”
Section: Introductionmentioning
confidence: 99%